Minimal impact of COVID-19 outbreak on the postoperative morbidity and mortality following emergency general surgery procedures: results from a 3-month observational period - Charalampos Seretis; Lucy Archer; Lida Lalou; Shuker Yahia; Christian Katz; Iram Parwaiz; Altaf Haji; Lourdusamy Selvam (Medicinski glasnik, 2020)
Aim: The outbreak of the COVID-19 pandemic has had a major impact on the delivery of elective, as well as emergency surgery on a worldwide scale. Up to date few studies have actually assessed the impact of COVID-19 on the postoperative morbidity and mortality following emergency gastrointestinal surgery. Herein, we present our relevant experience over a 3-month period of uninterrupted provision of emergency general surgery services in George Eliot Hospital NHS Trust, the United Kingdom. Methods: We performed a retrospective analysis of a prospective institutional database, which included the operation types, paraclinical investigations and postoperative complications of all patients undergoing emergency general surgery operations between March-May 2020. Results: The occurrence of a 5% overall respiratory complication rate postoperatively, with 3% infection rate for COVID-19 was found; no patient had unplanned return to intensive care for ventilator support and there was no mortality related to COVID-19 infection. Conclusion: When indicated, emergency surgery should not be delayed in favour of expectant/conservative management in fear of COVID-19-related morbidity or mortality risks.
Keywords: emergency; SARS-CoV-2; surgery